Early follow-up in the cardiological day hospital after heart surgery. Impact on hospital readmissions and emergency room visits. (14th October 2021) - Vaqueriza Cubillo, D; Gomez Mariscal, E; Dominguez Munoa, M; Beltran Herrera, C; Suberviola Sanchez-Caballero, V; Cano Moracho, J.M; Giganto Arroyo, M.L; Mora Yague, L; Jimenez Loeches, S; Sarrion Catala, M.M; Cortina Camarero, C; Cortes Beringola, A; et al.
Abstract: Introduction: In the first few months after heart surgery, readmissions and emergency visits are common. In order to reduce these events, we developed an early follow-up protocol after discharge based on attention in our cardiological day hospital (CDH), which allows clinical and analytical assessment, monitoring and intravenous treatment at successive visits. The objective of the study is to assess the effectiveness of the protocol after its implementation. Methods: Patients in our area discharged after heart surgery between 2013 and 2017 were included. They were divided into two groups, one with conventional follow-up and one with initial follow-up in CDH. Baseline clinical characteristics, type of surgery and surgical risk were compared. The primary endpoint was the time to the first readmission or emergency visit. The follow-up time was 200 days from discharge. Quantitative variables were compared using Student's t test and categorical variables using chi-square test. Cox proportional hazards model was used for multivariate analysis. Results: 321 patients, 160 with conventional and 161 with CDH follow-up, were included. There were no differences in baseline characteristics (age, type of surgery, comorbidities, risk and hospital stay) except for sex (44.7% women in conventional group vs 33.8% in HDC, p=0.04). The results of readmissions and the composite endpoint (readmission or emergency visit) at 30, 90 and 200 days are shown in the table. We found a trend of decreasing events in the CDH group, although statistical significance was not achieved. In multivariate analysis, the variables independently associated (p<0.05) with an increase in the combined endpoint at 200 days were: female sex, prior atrial fibrillation, hypertension and an Euroscore surgical risk index greater than 3. The time to a first cardiological assessment after discharge decreased significantly in the CDH group (58 vs 18 days, p<0.001). Conclusions: In patients followed in CDH after heart surgery, there is a trend towards less readmissions and emergency visits in the first six months after discharge. Some baseline characteristics have been shown to be independently associated with the risk of events, which will help us to identify the most at-risk patients, on which an intervention could have a greater magnitude of benefit. Funding Acknowledgement: Type of funding sources: None.